2020
DOI: 10.3389/fphys.2020.00100
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Tyrosinase Gene Plays a Potential Role in Modification the Shell Organic Matrix of the Triangle Mussel Hyriopsis cumingii

Abstract: Although tyrosinases have been speculated to participate in the shell formation of mollusks, there is still a lack of experimental evidence to support this assumption. In this study, a novel tyrosinase designated HcTyr2 was isolated and characterized from the freshwater mussel Hyriopsis cumingii. The change in HcTyr2 mRNA expression during the process of embryonic development was detected by real-time quantitative PCR. The result showed that the expression of HcTyr2 mRNA was significantly upregulated at the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…These data indicate expression of TYR, a key gene in matrix deposition, represents a significant target for BPA in Mytilus early larval development. However, tyrosinases participate in the cross-linking and maturation of shell matrix proteins by catalysing the quinoprotein oxidation(Ren et al, 2020). Therefore, BPA may act on other process upstream of matrix deposition and more directly responsible for the initial shell patterning.…”
mentioning
confidence: 99%
“…These data indicate expression of TYR, a key gene in matrix deposition, represents a significant target for BPA in Mytilus early larval development. However, tyrosinases participate in the cross-linking and maturation of shell matrix proteins by catalysing the quinoprotein oxidation(Ren et al, 2020). Therefore, BPA may act on other process upstream of matrix deposition and more directly responsible for the initial shell patterning.…”
mentioning
confidence: 99%
“…How SMPs construct a matrix framework and how SMPs regulate biomineral deposits is not fully understood. Tyrosinase is a popular SMP with a bivalves-specific expansion (Aguilera et al, 2014;Du et al, 2017;Huang et al, 2017) and plays an important role in shell formation (Zhang et al, 2012;Du et al, 2017;Ren et al, 2020). In our previous study, 12 tyrosinase including 2 NLSTyr's were identified from the shell organic matrix protein in P. f. martensii (Du et al, 2017).…”
Section: Discussionmentioning
confidence: 97%
“…For example, in pearl oyster and mussels, tyrosinases have been identified from the shell of their prismatic layer and nacreous layer (Du et al, 2017). The silencing of tyrosinase directly causes the disordered growth of the nacreous layer in Hriopsis cumingii (Ren et al, 2020). These results indicate that the expansion of tyrosinases generate novel functions rather than catalysis and directly participates in the formation of calcified shells.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proven to be served as the calcium ion transporter during shell formation in a variety of shellfish (Huang et al, 2007;Sun et al, 2015;Jain et al, 2017). In molluscs, tyr is strongly expressed in the edge of the mantle, which is the main biomineralization tissue, and tyrosinase proteins have also been detected in the proteome of the shell prismatic layer and nacreous layer, indicating its key role in the shell matrix deposition (Huan et al, 2013;Miglioli et al, 2019;Ren et al, 2020;Zhu et al, 2021). Moreover, tyrosinase was confirmed to participate in the embryo shell ontogeny of the organic matrix in M. galloprovincialis and Hyriopsis cumingii (Miglioli et al, 2019;Ren et al, 2020).…”
Section: Search For Degs Associated With Biomineralizationmentioning
confidence: 99%
“…In molluscs, tyr is strongly expressed in the edge of the mantle, which is the main biomineralization tissue, and tyrosinase proteins have also been detected in the proteome of the shell prismatic layer and nacreous layer, indicating its key role in the shell matrix deposition (Huan et al, 2013;Miglioli et al, 2019;Ren et al, 2020;Zhu et al, 2021). Moreover, tyrosinase was confirmed to participate in the embryo shell ontogeny of the organic matrix in M. galloprovincialis and Hyriopsis cumingii (Miglioli et al, 2019;Ren et al, 2020). In M. lateralis, the expression pattern of these two genes was obviously upregulated in D-shaped larva.…”
Section: Search For Degs Associated With Biomineralizationmentioning
confidence: 99%